2013
DOI: 10.1007/s12550-013-0162-2
|View full text |Cite
|
Sign up to set email alerts
|

Gliotoxinogenic Aspergillus fumigatus in the dairy herd environment

Abstract: The potential association between hygienic conditions in the environment of lactating cows and the presence of gliotoxinogenic Aspergillus fumigatus strains was studied. Milk samples (individual cow's milk [ICM], bulk tank milk [BTM]) from 44 dairy farms were sampled. In ICM samples, eight different species of Aspergillus were identified. A. flavus and A. fumigatus were predominant, with 37.8% and 26.1% relative densities, respectively. A. fumigatus strains were isolated from 61.4% of the BTM samples, and 34% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…They had previously been characterized as gliotoxin producers (Pellegrino et al . ). The silage samples were collected from a feed plant located in the south of Córdoba Province in 2011.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…They had previously been characterized as gliotoxin producers (Pellegrino et al . ). The silage samples were collected from a feed plant located in the south of Córdoba Province in 2011.…”
Section: Methodsmentioning
confidence: 97%
“…These isolates were kept in the National University of R ıo Cuarto, C ordoba, Argentina (RC) Collection Centre. They had previously been characterized as gliotoxin producers (Pellegrino et al 2013). The silage samples were collected from a feed plant located in the south of C ordoba Province in 2011.…”
Section: Fungal Isolatesmentioning
confidence: 99%
“…Moreover, the study identified an association between the presence of A. fumigatus and the severity of respiratory distress in the calves. Another study by 23 investigated the pathogenicity of A. fumigatus in dairy calves. The study found that A. fumigatus was capable of causing severe lung lesions and mortality in experimentally infected calves.…”
Section: Eukaryotic Infections In Dairy Calvesmentioning
confidence: 99%
“…Diagnosis is typically made through more advanced diagnostic techniques such as PCR and ELISA. 23 Preventing and controlling Eimeria spp infections in dairy calves is critical to maintaining calf health and reducing economic losses. Management practices, such as proper sanitation and hygiene, can help reduce the risk of Eimeria infection.…”
Section: Protozoa Infectionsmentioning
confidence: 99%
“…In contrast, other mycotoxins such as deoxynivalenol and zearalenone, are found in milk only in low concentrations [ 18 ]. This applies also to gliotoxin [ 19 ].…”
Section: Mycotoxins In Cow As Well As Ovine Milkmentioning
confidence: 99%